IMPLEMENTASI KURIKULUM HOLISTIK UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PADA SISWA MADRASAH TSANAWIYAH (MTs) DI BANJARMASIN - Salamah Salamah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2015)
The learning outcomes of Islamic Religious Education (PAI) in Madrasah is often considered minimum. Holistic curriculum is believed to be relevant and can be an alternative solution to overcome the problem of learning school in relation to the improvement of learning outcomes. Holistic curriculum model is based on the perennial philosophy. It is a school that sees education as a cultural heredity / a whole, integrated, and relevant discipline which presents the related, connected and intact teaching materials. The implementation process uses an active and cooperativeapproach which integrates learning with logical thinking, intuition, emotion and directexperience. By using classroom action research procedure, this model was implemented to find a model that is relevant to the characteristics of PAI at MTs. The experimental research was also carried out to look at the effectiveness of the curriculum used. The results showed thatthe experimental group gained greater learning outcomes (high category), than the control class. The students activity inlearning process of the experimental class also showed higher level of participation than the control class.